2021
DOI: 10.24018/ejmed.2021.3.1.717
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Spermatic Cord Twisting: Experience of the University Hospital Center of Casablanca

Abstract: Introduction: Spermatic cord twisting (SCT) is a life-threatening emergency of the testis, causing testicular ischemic lesions by vascular constriction. Neglected SCT is an atypical variant of torsion with a late diagnostic delay. It is characterized by the presence of testicular necrosis, requiring an orchiectomy. The objective of our study is to investigate possible factors that may be responsible for the delayed diagnosis of TCS, and thus favor the occurrence of the neglected form. In order to act on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In France, the average presentation time reported in a multicenter study was 5 h [34]. In Morocco, in a study of neglected testicular torsions, the mean time to presentation was reported to be 86 h [35]. In a systematic review including 2116 patients, testicular recovery within the first 12 h was 90.4%, survival from 13 to 24 h was 54.0% and survival beyond 24 h was 18.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In France, the average presentation time reported in a multicenter study was 5 h [34]. In Morocco, in a study of neglected testicular torsions, the mean time to presentation was reported to be 86 h [35]. In a systematic review including 2116 patients, testicular recovery within the first 12 h was 90.4%, survival from 13 to 24 h was 54.0% and survival beyond 24 h was 18.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Torsion is a time-dependent event, and factors (distance from hospital and delay associated with transfer to hospital) that delay time to treatment result in a high rate of testicular loss [36]. El Mehdi et al [35] reported that 15% of their patients with testicular loss were from rural areas. We found an association between the mode of admission and the probability of testicular salvage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation